The Influence of Kaizen Culture and Rewards on Employee Performance at PT. Pardic Jaya Chemicals - Ananda Prassetiyo; Ulta Rastryana; Usran Masahere; Syabrinildi (The Future of Education Journal, 2025)
PT. Pardic Jaya Chemicals is a company that produces synthetic resin used as raw material for other industries. In its operations, it is important for PT. Pardic Jaya Chemicals to pay attention to factors that can optimize employee performance, such as the kaizen culture implemented through a suggestion system and a reward system. The purpose of this study is to analyze the partial and simultaneous effects of kaizen culture and rewards on employee performance. The data collection methods used are observation, questionnaires, and literature study. The type of analysis method is quantitative, using multiple linear regression analysis. The sample size is 60 people, obtained from the Slovin formula applied to a population of 150 individuals. Based on the research conducted, the multiple linear regression equation produced is Y = 5.611 + 0.290X1 + 0.557X2. This equation shows that kaizen culture has a positive and significant effect on employee performance with a significance value of 0.002 < 0.05 and t-count > t-table (3.317 > 2.002). Rewards have a positive and significant effect on employee performance with a significance value of 0.001 < 0.05 and t-count > t-table (4.965 > 2.002). Kaizen culture and rewards simultaneously have an effect on employee performance with a significance value of 0.001 < 0.05 and F-count > F-table (36.988 > 4.007).